2020
DOI: 10.1002/ente.202000842
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress on Photo‐Promoted Alcohol Electrooxidation for Fuel Cells

Abstract: Alcohol electrooxidation reaction (AOR) is of sluggish kinetics, which as the anodic reaction of direct alcohol fuel cells determines largely the discharging performance of the device. Solar energy as an endless energy source is introduced to promote the AOR kinetics. Herein, the recent progress on photopromoted AOR and the application in fuel cells is reviewed, including 1) design of the AOR photoelectrocatalysts, 2) photoelectrocatalysis mechanism, and 3) fabrication of photo-promoted direct alcohol fuel cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 102 publications
0
8
0
Order By: Relevance
“…Solar energy as an endless power is highly expected to be exploited to promote the efficiency of mass and energy conversions via photocatalysis. Ignited by the progress in photocatalysis, photoassisted electrocatalysis has gradually become an attractive approach to accelerate the reaction kinetics. Some reviews have summarized the recent progress in this field. For photoassisted electrocatalysis, the utilization efficiency of solar energy predominately depends on the efficiencies of light adsorption, photogenerated charge separation/transfer, and surface reaction, which in turn rely mainly on photocatalysts. Theoretically, semiconductors with a valence-band energy more positive than the Nernst potential of MOR are potentially capable of oxidizing methanol.…”
Section: Introductionmentioning
confidence: 99%
“…Solar energy as an endless power is highly expected to be exploited to promote the efficiency of mass and energy conversions via photocatalysis. Ignited by the progress in photocatalysis, photoassisted electrocatalysis has gradually become an attractive approach to accelerate the reaction kinetics. Some reviews have summarized the recent progress in this field. For photoassisted electrocatalysis, the utilization efficiency of solar energy predominately depends on the efficiencies of light adsorption, photogenerated charge separation/transfer, and surface reaction, which in turn rely mainly on photocatalysts. Theoretically, semiconductors with a valence-band energy more positive than the Nernst potential of MOR are potentially capable of oxidizing methanol.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, to solve the above problems, some new bimetallic catalysts such as Pt–Ru, Pt–Ag, and Pt–Pd have been investigated to improve ethanol gas sensors’ performance. , …”
Section: Fundamental Of Fuel-cell-type Gas Sensorsmentioning
confidence: 99%
“…Moreover, alcohols have been considered as one of the most prominent sacrificial agents, which can result in an increase in PEC activity based on the "current-doubling" effect. [170,171] This phenomenon implies that each one absorbed photon can inject two electrons, thanks to the photogeneration and the intermediate radical formation from alcohols oxidation. When considering PEC approach, it is attributed to the multitimes increase in current density produced in water splitting reaction with the presence of alcohols in the electrolyte.…”
Section: Promoting H 2 Productionmentioning
confidence: 99%
“…[175,177,200] Among the common photocatalysts, Fe 2 O 3 is the widely used semiconductor material for photoanode because of its favorable bandgap to visible-light adsorption and thermodynamical stability, which is promising to catalyze MOR. [171,[200][201][202][203][204] Mesa et al [200] reported a study case of the selective oxidation of CH 3 OH to HCHO based on Si-doped Fe 2 O 3 photoanode with near-unity FE(HCHO) at 96% and only required less 270 mV onset potential than that for water oxidation. The rate of MOR was determined to be the second order in the density of surface holes, indicating the dependency upon the photoanode design (e.g., surface area) and optimum operational light intensities.…”
Section: Higher Value-added Productionmentioning
confidence: 99%